A genome-wide association study provides insights into fatty acid synthesis and metabolism in Malus fruits. (16th September 2022) - Jiang, Lijuan; Geng, Dali; Zhi, Fang; Li, Zhongxing; Yang, Yusen; Wang, Yunlong; Shen, Xiaoxia; Liu, Xiuyun; Yang, Yanqing; Xu, Yange; Tang, Yanlong; Du, Rui; et al.
Abstract: As a precursor of aromatic compounds, fatty acids play important roles in apple fruit quality; however, the genetic and molecular basis underlying fatty acid synthesis and metabolism is largely unknown. In this study, we conducted a genome-wide association study (GWAS) of seven fatty acids using genomic data of 149 Malus accessions and identified 232 significant signals (–log10 P >5) associated with 99 genes from GWAS of four fatty acids across 2 years. Among these, a significant GWAS signal associated with linoleic acid was identified in the transcriptional regulator SUPERMAN-like ( SUP ) MD13G1209600 at chromosome 13 of M. × domestica . Transient overexpression of MdSUP increased the contents of linoleic and linolenic acids and of three aromatic components in the fruit. Our study provides genetic and molecular information for improving the flavor and nutritional value of apple. Abstract : A genome-wide association study in apple identifies SUPERMAN-like ( SUP ) that affects the contents of linoleic acid, linolenic acid, and three aromatic components of the fruit.